The role of institutions within the IPR enforcement: The case of de facto software protection in Egypt - Nora El-Bialy (Philipps-University Marburg, Department of Technology and Innovation Management, 2010)
The present paper develops a new institutional perspective of intellectual property right (IPR) enforcement dilemmas in developing countries, focusing on the case of software protection in Egypt. Transplanting western made IPR rules and enforcement strategies to developing countries without any additional assistance from right holders did not fulfill the required enforcement standards. Satisfactory results can only be achieved gradually. Game theoretical examinations showed that decisions tak en by both parties (right holders and developing countries) under the homo-economicus assumption and in the absence of binding institutions lead to inefficient outcomes, while agreeing on a long-term cooperative second best mindset leads to higher welfare gains. In order to maintain a stable contractual outcome to enforce IPR, one should control for the process of structuring de facto institutions, especially enforcement authorities (prosecutors and judiciary) before signing the agreement and throughout the contractual phase. This hinders sharp fluctuations of transaction cost (TC) and expected value of future payoffs that might occur during the different stages of the contract. Accordingly, the paper provides a new policy tool that can be considered useful when discussing new strategies related to the possibility of establishing binding institutions to enforce IPR.
Keywords: 650; Intellectual Property Rights (IPR); De jure versus De facto protection; Institutions; Software Piracy